Pengaruh Pemberian Ekstrak Biji Klabet (Trigonella foenum-graecum L.) Terhadap Kadar Hormon Estradiol Dan FSH Plasma Tikus Putih Betina Galur Wistar Prepubertal - Agustini, Kurnia; Wiryowidagdo, Sumali; Kusmana, Dadang (Majalah Ilmu Kefarmasian, 2005)
Biji Klabet or Fenugreek (Trigonella foenum-graecum L.) contains steroidal sapogenins such as diosgenin, tigogenin, gitogenin, yamogenin and trigoneoside, that are suspected having an estrogen-like effect or as phytoestrogen. The objective of this study was to evaluate the estrogen-like effect of biji klabet alcohol extracts. This research used immature Wistar female rats, age of 19 days, which were represent the climacteric/menopause phase. The testing animals were divided into five groups, namely normal group, estradiol control group and three level dose groups of fenugreek extract (30 mg/200 gBW; 60 mg/200 gBW and 120 mg/200 gBW). The result showed that on 120 mg/200 gBW fenugreek extract significantly (a=0.05) increased estradiol and FSH level on immature rat. Analysis of vaginal smear showed vaginal lubrication effect, surprisingly on 120 mg/200 gBW could induce estrous cycle.